Irregular Attractors - Vadim S. Anishchenko; Galina I. Strelkova (Discrete Dynamics in Nature and Society)
In this paper the definition of attractor of a dissipative dynamical system is introduced. The classification of the existing types of attractors and the analysis of their characteristics are presented. The discussed problems are illustrated by the results of numerical simulations using a number of real examples that provides the possibility to understand easily the main properties, similarities and differences of the considered types of attractors.